2021
DOI: 10.1108/afr-06-2021-0078
|View full text |Cite
|
Sign up to set email alerts
|

Financial literacy and its determinants: the case of rural farm households in Ghana

Abstract: PurposeThis paper aims to examine the determinants of rural dwellers financial literacy in Ghana.Design/methodology/approachA cross-sectional primary data set was used to estimate the factors influencing rural farm households' financial literacy using the IV-Tobit model.FindingsThe findings reveal that most rural residents are financially illiterate. The econometrics model results depicted that respondents' socioeconomic and demographic characteristics such as gender, income, age and education significantly af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 45 publications
3
26
0
Order By: Relevance
“…The numbers of studies on the issue of FL amongst farmers are scanty in the scholarship. Akoto et al (2017) and Twumasi et al (2021) observed the prevalence of poor FL (affected by age, economic status, educational attainment, gender, risk tolerance and viewership of FL television programmes) amongst Ghanaian farmers. On the other hand, Widhiyanto et al (2018), Santoso et al (2020) and Safitri (2021) noticed that the moderate FL amongst the Indonesian farmers geting affected by age, educational attainment, level of income, financial inclusion (FI) and FL training.…”
Section: Brief Review Of Literaturementioning
confidence: 99%
“…The numbers of studies on the issue of FL amongst farmers are scanty in the scholarship. Akoto et al (2017) and Twumasi et al (2021) observed the prevalence of poor FL (affected by age, economic status, educational attainment, gender, risk tolerance and viewership of FL television programmes) amongst Ghanaian farmers. On the other hand, Widhiyanto et al (2018), Santoso et al (2020) and Safitri (2021) noticed that the moderate FL amongst the Indonesian farmers geting affected by age, educational attainment, level of income, financial inclusion (FI) and FL training.…”
Section: Brief Review Of Literaturementioning
confidence: 99%
“…The third path shows that IT can enhance financial skills and knowledge. As people acquire financial information and managerial skills through financial education, they become confident to participate in the financial market to create wealth (Ankrah Twumasi et al, 2021a;Riebe, 2021;Khan and Surisetti, 2021). Finally, the study showed that IT provides business/market information.…”
Section: The Impact Of Information Technology (It) On Incomementioning
confidence: 99%
“…Wages/salaries, rent, remittances, pensions, and dividends are all examples of off-farm income. Other variables (e.g., age, gender, education, farming experience, distance from farmers' residence to the nearest financial institution, financial literacy, and household size) were added as control variables after following other literature (e.g., Ankrah Twumasi et al, 2021a;Siaw et al, 2020) and our available data (see Table 8.1 for the definition of the other control variables). Also, see Table A1 in the Appendix to see how financial literacy was measured.…”
Section: Key Variables Selection and Definitionmentioning
confidence: 99%
“…This study explores the effect of FL on household income using AFS and social networks as a mediator and moderator, respectively. This study’s financial literacy measurement was calculated using seven quiz-like questions employed by many scholars (Andoh et al, 2015; Ankrah Twumasi et al, 2021; Lusardi & Mitchell, 2007; Niu & Zhou, 2018). We assigned the value of 1 to a correct answer and 0 to an incorrect answer, suggesting that the FL score will range from 0 to 7.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…Finally, from the theory of social networking, the author tries to test social networks (whether a household has a link with a FI official) as a moderator for the financial literacy-AFS relationship. It is believed that individuals take precautional measures when dealing in the financial market to be successful in their financial decision (Ankrah Twumasi et al, 2021; Bucher-Koenen et al, 2017). Therefore, knowing an expert or relating to someone already an official in the financial market becomes a plus for the individual willing to participate in the market.…”
Section: Introductionmentioning
confidence: 99%